Systematic Literature Review: Metode Deteksi Dini Diabetes Mellitus Gestasional - Rizky Vaira; Merlin Karinda (Yayasan Literasi Sains Indonesia, 2022)
Gestational Diabetes Mellitus (GDM) is one of the medical complications of pregnancy that can cause short-term and long-term risks for the mother and fetus if not detected early and treated appropriately. This study aims to find, select, assess, extract, and synthesize data from several articles on the method of early detection of GDM that can be carried out by health workers. This study uses a systematic literature review method with the PICO framework. Search articles using PubMed and Science Direct databases with keywords and Boolean operators in this study are